2010
DOI: 10.1186/1477-7525-8-99
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between adherence rates measured by MEMS and self-reported questionnaires: a meta-analysis

Abstract: PurposeIt is vital to understand the associations between the medication event monitoring systems (MEMS) and self-reported questionnaires (SRQs) because both are often used to measure medication adherence and can produce different results. In addition, the economic implication of using alternative measures is important as the cost of electronic monitoring devices is not covered by insurance, while self-reports are the most practical and cost-effective method in the clinical settings. This meta-analysis examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 39 publications
5
124
1
6
Order By: Relevance
“…A meta-analysis found self-report to be a good estimate of patient adherence when compared with electronic monitoring. 39 The good correlation between self-report and refill adherence found in our study and reported elsewhere [40][41][42] supports the validity of these two measures. In combination, they can assist in achieving an accurate measure for patient adherence.…”
Section: Discussionsupporting
confidence: 71%
“…A meta-analysis found self-report to be a good estimate of patient adherence when compared with electronic monitoring. 39 The good correlation between self-report and refill adherence found in our study and reported elsewhere [40][41][42] supports the validity of these two measures. In combination, they can assist in achieving an accurate measure for patient adherence.…”
Section: Discussionsupporting
confidence: 71%
“…Among comparisons that were not highly concordant, self-reports produced higher estimates of adherence than other assessment methods 92 % of the time (45 out of 49 comparisons). A meta-analysis showed the estimated degree of regimen execution is approximately 15 % higher by self-report when compared with EDM devices [56], which is consonant with estimates in other reviews and syntheses [5,35,56,58].…”
Section: Validity Of Medication Adherence Self-reportssupporting
confidence: 79%
“…In a review of 41 medication adherence studies, Shi and colleagues [55] determined that a majority of studies (68 %) report correlations between self-report and EDM adherence measures that are either high (27 %), moderate (29 %), or low yet statistically significant (12 %). A related metaanalysis estimated that the pooled correlation coefficient between self-report and electronically monitored adherence was 0.45 (95 % CI, 0.34-0.56) [56].…”
Section: Practice and Public Health Policiesmentioning
confidence: 99%
See 2 more Smart Citations